ANALISIS USAHATANI BEBERAPA VARIETAS PADI DENGAN MENGGUNAKAN REVENUE COST RATIO (R/C RATIO) - Untari Untari (AGRICOLA, 2014)
This study aims to analyze the feasibility of paddy farming system for several varieties are Maraoke, Dyah Suci, Ciliwung, Inpago Unsoed 1 and Inpago JSPGA 136 using Revenue Cost Ratio (R/C Ratio) in Merauke District. The research was conducted in Marga Mulya, Semangga Sub-district starts from September 2012 to Januari 2013.Analysis data used feasibility of farming system.The results showed that the rice varieties of inpago JSPGA Unsoed 1 and Inpago 136 recommended to developed in Merauke District. The R/C Ratio forInpago Unsoed 1 was 3,14 and Inpago JSPGA 136 was  3,47.Meanwhile, R/C Ratio for variety Meraoke, Dyah Suci and Ciliwung respectively is 1.55, 2.70, and 3.45.